2003
DOI: 10.1002/lsm.10212
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro percutaneous penetration of 5‐aminolevulinic acid and two of its esters through excised hairless mouse skin

Abstract: The differences in skin penetration properties could be (co-)responsible for the finding that ALA esters do not induce substantially higher PpIX levels in in vivo skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…46,47 In this study, possible explanations to the presence of PPIX at the relatively large depths might be increased drug diffusivity and skin permeability achieved by the use of ALA-ME, and the removal of crust and the superficial skin layer. 48 The negative correlation between the light transmission and the sensitizer fluorescence level remaining at the end of the treatment indicates more efficient photobleaching during treatments characterized by a smaller increase in tissue absorption. This result might not seem very surprising, since a higher irradiance photobleaches the sensitizer more efficiently, given a sufficient oxygen concentration.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 In this study, possible explanations to the presence of PPIX at the relatively large depths might be increased drug diffusivity and skin permeability achieved by the use of ALA-ME, and the removal of crust and the superficial skin layer. 48 The negative correlation between the light transmission and the sensitizer fluorescence level remaining at the end of the treatment indicates more efficient photobleaching during treatments characterized by a smaller increase in tissue absorption. This result might not seem very surprising, since a higher irradiance photobleaches the sensitizer more efficiently, given a sufficient oxygen concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have shown that upon topical application of ALA to normal skin, the presence of the stratum corneum is an important limiting factor for PpIX production [13,14], in vivo ALA penetration through skin [15] and in vitro ALA penetration through skin [16]. The barrier function of the stratum corneum against ALA penetration into the skin is very effective and is determined by the structure and composition of the stratum corneum.…”
Section: Introductionmentioning
confidence: 99%
“…Permeation enhancement across skin can vary from negligible to over an order of magnitude. Van den Akker et al [58] reported no significant increase in penetration of 5-aminolevulinic acid esters across mouse skin compared to the parent drug. In contrast, dialkylamnomethyl prodrugs of 6-mercaptopurine were found to have delivery rates up to 27-fold greater than the parent molecule [47].…”
Section: Prodrugsmentioning
confidence: 99%
“…The prodrug approach has been used to increase delivery of a range of drugs across the skin, including 6-mercaptopurine [47], 5-fluorouracil [48], naproxen [49,50]; kepoprofin [50]; diclofenac [50]; ketoralac [51], captopril [52], cyclosporine [53], buphenorphine [54], beta blockers [55], theophylline [56] and 5-aminolevulinic acid [57,58]. Permeation enhancement across skin can vary from negligible to over an order of magnitude.…”
Section: Prodrugsmentioning
confidence: 99%